Pengaruh Intensitas Penggunaan Fitur Close Friends Instagram Terhadap Self Disclosure (Survei Kepada Pengikut Akun Instagram @Titrasirasa) - Naura Khalisha Ramadhani (2022)
The rapid advancement of technology and information allows individuals to receive and send information quickly. The development of technology now demands us to be ready for changes that might happen. One of the results of the advancement of technology is social media. Today, the most popular social media among Indonesians is Instagram. Instagram provides several advantages, namely, as a medium for communicating using interactive pictures through several features offered, one of those is the Close Friends feature. This study aims to determine how much influence the Instagram close friends feature has on self-disclosure on followers of the @titrasirasa account. The method used in this study is a quantitative method, namely the data collection method in the form of a survey by distributing an online questionnaire in the form of a google form to followers of the @titrasirasa account. The data collection technique that the researcher uses is a purposive sampling technique, using the Taro Yamane formula and an error value of 10% of the sample to 100 respondents who are followers of the @titrasirasa account.Data analysis in this study used simple linear regression. The results obtained in this study indicate that there is a significant effect between the use of the close friends feature on self-disclosure. If it is associated with the Self Disclosure theory and the Johari Window theory, this research is included in the Open Self. This is because someone conveying information about personal matters can be known by themselves and others. Then, this area will usually vary in size depending on who someone is communicating with.